Perineal Laceration in primipara in Association with Perineal length, Fetal Head Circumference, and Fetal Weight - Claudio Udjaja; Erwinanto Erwinanto; Herman Kristanto; Hary Tjahjanto; Yuli Trisetiyono; Arufiadi Anityo Mochtar (Medica Hospitalia : Journal of Clinical Medicine, 2024)
BACKGROUND : Perineal laceration is one of the risk and complication of spontaneous labour resulting intervention in short-term and long-term quality of life. Lack of research in Indonesia on perineal length Lack of research on perineal length in Indonesia, fetal birth weight and fetal head circumference and its impact on spontaneous labour and perineal laceration gave rise to the idea of research in order to minimize the occurrence of complications from perineal laceration in spontaneous labour.OBJECTIVES : To know find out the association between perineal length, fetal head circumference, and fetal weight with degree of perineal laceration in primiparous women.METHODS : Observational cross sectional multi-center study conducted between August 2023 until October 2023 in which all subject that delivered vaginally within inclusion criteria was measured. All data will be further analized to determine the significant predictor of perineal tear.RESULTS : Based on this study The result of this study has indicated that there is no significant association of perineal length with the degree of spontaneous primiparous perineal laceration. While there is an association of fetal head circumference and fetal weight with the degree of spontaneous primiparous perineal laceration in aterm pregnancy. Based on further analysis, fetal head circumference greater than 325 mm increases the risk of severe perineal laceration 4.4 times (PR=4,4; 95% CI=1,4-13,9) and Fetal weight greater than 3097.5 grams increases the risk of 2.7 times (PR=2,7; 95% CI=1,1-6,4) the occurrence of severe perineal laceration.CONCLUSION : There is an association of fetal head circumference and fetal weight with the degree of spontaneous primiparous perineal laceration.